2020
DOI: 10.3390/ijerph17186445
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being of Female-Headed Households Based on Age Stratification: A Nationwide Cross-Sectional Study in South Korea

Abstract: The female-headed household is a new vulnerable group associated with health inequality. The purpose of this study was to analyze psychological well-being and related factors among Korean female-headed households based on age stratification. This was a secondary analysis of data extracted from the fifth Korean Working Conditions Survey (2017), which included a total of 9084 female-headed households. Their psychological well-being was measured by the WHO-5 well-being index. A total of 39.8% of female-headed hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(25 reference statements)
3
5
0
Order By: Relevance
“…Our results also indicated adequate negative correlations between well-being and anxiety, consistent with a previous study that found strong correlations between the WHO-5 Well-Being Index and anxiety [ 29 ]. Additionally, adequate negative correlations were found between well-being and depression, consistent with previous studies reporting that the WHO-5 correlated negatively with depression [ 28 , 47 , 48 , 49 , 50 , 51 , 52 ]. Together with the obtained internal consistency values, these findings support the construct validity of the well-being scale.…”
Section: Discussionsupporting
confidence: 89%
“…Our results also indicated adequate negative correlations between well-being and anxiety, consistent with a previous study that found strong correlations between the WHO-5 Well-Being Index and anxiety [ 29 ]. Additionally, adequate negative correlations were found between well-being and depression, consistent with previous studies reporting that the WHO-5 correlated negatively with depression [ 28 , 47 , 48 , 49 , 50 , 51 , 52 ]. Together with the obtained internal consistency values, these findings support the construct validity of the well-being scale.…”
Section: Discussionsupporting
confidence: 89%
“…They found that individual problems, intra-family problems, social problems, and positive outcomes. Kim et al (2020) analyzed psychological welfare and related factors among female-headed households in Korea. They found that 39.8% of households headed by female workers were psychologically unhealthy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study analysed psychological well-being and related factors among Korean female-headed households based on age stratification. The psychological well-being perceived by female households is complex and goes beyond socio-economic poverty and dependent burdens (Kwon & Kim, 2020). Ratwatte (2021) stated that in Sri Lanka, over 25% of the households (i.e.…”
Section: Review Of Literaturementioning
confidence: 99%